(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to improve the forward roll floor gymnastics ability of class VII students of SMP Negeri 3 Palembang through the Play Approach. Improving learning outcomes, students can be measured from the test results obtained from cycle I and cycle II. Study this, including the type of classroom action research with collaboration between researchers and colleagues as observers. The research subjects were 30 students of class VII of SMP Negeri 3 Palembang in the 2024 academic year. Students’ initial abilities regarding floor gymnastics movements without equipment were very low. This was proven by test results before the average improvement of the class was only 52.43, and only 11 people whose scores were > KKM 75. The gymnastic movements performed were jumping on the spot, standing on the head, and standing on the hands. The results of this study indicate that the teaching and learning process has increased from before the improvement, cycle I and cycle II, as evidenced by the average class achieved by students before the improvement was only 52.43 with the criteria of less, cycle I reached 72.43 with the criteria of sufficient and cycle II reached an average class of 81.00 with the criteria of "Good". While the target for achieving KKM, before the action was 30%, in cycle I increased to 65% and in cycle II the completeness increased again to 94%. Based on the analysis, the data can conclude that learning exercises floor without a tool. Through the Play Approach, learning outcomes of class VII students at SMP Negeri 3 can be improved. Palembang. The increase in the achievement of KKM from before the improvement to cycle II reached 55%. So this research is considered complete because the students’ classical abilities have increased > KKM.